2004
DOI: 10.1074/jbc.m408682200
|View full text |Cite
|
Sign up to set email alerts
|

Glucose-stimulated Protein Synthesis in Pancreatic β-Cells Parallels an Increase in the Availability of the Translational Ternary Complex (eIF2-GTP·Met-tRNAi) and the Dephosphorylation of eIF2α

Abstract: In pancreatic ␤-cells, glucose causes a rapid increase in the rate of protein synthesis. However, the mechanism by which this occurs is poorly understood. In this report, we demonstrate, in the pancreatic ␤-cell line MIN6, that glucose stimulates the recruitment of ribosomes onto the mRNA, indicative of an increase in the rate of the initiation step of protein synthesis. This increase in the rate of initiation is not mediated through an increase in the availability of the initiation complex eIF4F, because gluc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
46
0

Year Published

2005
2005
2014
2014

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 47 publications
(50 citation statements)
references
References 55 publications
4
46
0
Order By: Relevance
“…An mTOR independency of eIF2α (de)phosphorylation has been noticed in other cells [36,37]. The glibenclamideinduced dephosphorylation of eEF2 was almost completely prevented by the PKA inhibitor, indicating the existence of an additional way in which PKA stimulates translation.…”
Section: Discussionmentioning
confidence: 68%
“…An mTOR independency of eIF2α (de)phosphorylation has been noticed in other cells [36,37]. The glibenclamideinduced dephosphorylation of eEF2 was almost completely prevented by the PKA inhibitor, indicating the existence of an additional way in which PKA stimulates translation.…”
Section: Discussionmentioning
confidence: 68%
“…Since it has been shown that glucose starvation can have a suppressive effect on translation under normoxic conditions in certain cell lines (Gomez et al 2004;Vander Mierde et al 2007) we wanted to determine if the translational repression that we observe under hypoxic conditions is merely a consequence of glucose depletion. Our data clearly show that short-term (20 h) glucose depletion under normoxic conditions has little impact on protein synthesis while dramatically inhibiting translation under hypoxic conditions.…”
Section: Discussionmentioning
confidence: 99%
“…This indicates that glucose stimulates the recruitment of ribosomes on to mRNAs and hence stimulates an increase in the rate of initiation. Indeed, we have recently shown that glucose stimulates an increase in the initiation step of protein synthesis in MIN6 cells [19]. At low glucose concentration, proinsulin mRNA was found to cosediment with either monosomes or small polysomes (Figures 4ai and 4ii).…”
Section: Glucose Stimulates the Recruitment Of Ribosomes On To Ribosomentioning
confidence: 99%
“…Anti-SRP54 antibody was purchased from Becton Dickinson (Cowley, Oxford, U.K.). Western blotting, SDS/PAGE and immunoprecipitations were performed as described previously [19].…”
Section: Sds/page Western Blotting and Immunoprecipitationmentioning
confidence: 99%